The roles of teacher and parental support on adolescent cyber-bystander behaviors: a path analysis - Chen, Qiqi; Wu, Qianru (Frontiers in Psychology, 2024)
Introduction The role of bystanders in cyberbullying situations is critical, with the potential to significantly influence outcomes. Bystanders who demonstrate positive behaviors—such as reporting incidents or supporting victims—can help to mitigate the damaging effects of cyberbullying. Based on the Social Cognitive Theory, this study seeks to address the psychosocial mechanisms that underlie positive cyber-bystander behaviors. Methods A total of 1,716 students in Grades 8–12 from three secondary schools in China participated in this study. Path analysis was utilized to delineate the relationships between internet self-efficacy, empathy, teacher and parental support, and cyber-bystander behaviors. Results Adolescents who received greater support from teachers were more likely to demonstrate increased internet self-efficacy and empathy. In contrast, higher levels of parental warmth were associated with lower levels of internet self-efficacy. Teacher support and parental warmth exerted an indirect effect on positive bystander behaviors through empathy. Discussion The importance of parental warmth paired with Internet self-efficacy in preventing online interpersonal violence and motivate active bystander behaviors is considerable. We recommend adopting a nuanced approach that differentiates between empathy and internet self-efficacy in cyber-bystander research.